Arousing Learner Interest and Engagement in a Multilingual Classroom Context: English Second Language Teachers’ Experiences and Strategies - Sboniso Praisegod Zondi; Siphelele Mbatha (E-Journal of Humanities, Arts and Social Sciences, 2024)
Teaching English as a Second Language (ESL) to learners of different basic schooling phases is arguably an interesting yet enigmatic phenomenon, which features a variety of factors such as language diversity, curriculum, policy, and cultural factors. This paper sought to explore the experiences and the strategies employed by ESL teachers to aid learners in navigating through linguistic diversity in English Second Language classroom contexts. From the interpretivist epistemological stance, the researchers inferred qualitative data through semi-structured interviews from ten (10) purposively sampled high school ESL teachers from one district in Durban. Data was thematically analysed through the Social Constructivist Theory. The study’s findings indicated that the primary approach used by ESL teachers in linguistically diverse classrooms was various languages in English literature classrooms. Furthermore, the study discovered that using various languages arouses learners’ interests and enhances learner involvement in classroom-based activities. In this regard, the researchers concluded that learners are more engaged and motivated to learn to read, analyse and respond to texts in a multilingual classroom than in monolingual classrooms. The researchers further recommend that teachers use strategies beyond the textbook and policy documents to capture the learner’s attention. Using various teaching approaches, codeswitching, and translanguaging are effective strategies teachers and the Department of Education should not shy away from.